Overcoming variant mutation-related impacts on viral sequencing and detection methodologies - Bei, Yanxia; Pinet, Kaylinnette; Vrtis, Kyle B.; Borgaro, Janine G.; Sun, Luo; Campbell, Matthew; Apone, Lynne; Langhorst, Bradley W.; Nichols, Nicole M. (Frontiers in Medicine, 2022)
Prompt and accurate pathogen identification, by diagnostics and sequencing, is an effective tool for tracking and potentially curbing pathogen spread. Targeted detection and amplification of viral genomes depends on annealing complementary oligonucleotides to genomic DNA or cDNA. However, genomic mutations that occur during viral evolution may perturb annealing, which can result in incomplete sequence coverage of the genome and/or false negative diagnostic test results. Herein, we demonstrate how to assess, test, and optimize sequencing and detection methodologies to attenuate the negative impact of mutations on genome targeting efficiency. This evaluation was conducted using in vitro-transcribed (IVT) RNA as well as RNA extracted from clinical SARS-CoV-2 variant samples, including the heavily mutated Omicron variant. Using SARS-CoV-2 as a current example, these results demonstrate how to maintain reliable targeted pathogen sequencing and how to evaluate detection methodologies as new variants emerge.